THE URGENCY OF IMPLEMENTING A GREEN ECONOMY FROM THE PERSPECTIVE OF THE DHARURIYAH APPROACH IN MAQASHID AL-SHARIAH - Fauzia, Ika Yunia (Universitas Airlangga, 2016)
The green economy is a concept that supports human welfare, environmental sustainability, and ecosystems. This is evidenced by its slogan, which is pro-growth, pro-poor, pro-job, and pro-environment. The green economy is in line with the objectives, basic principles, and systems of Islamic economics, which is to improve human welfare in line with improving the quality of life of humans and nature. The discussion of the objectives of shariah (maqashid al-shariah) is interesting to be used as an analytical tool in approaching the study of the green economy. Therefore, this study, using the library research method, reveals the concept of the green economy from the perspective of maqashid al-shariah. Through content analysis, it was concluded that there is a need to add hifz al-bi'ah (preservation of the environment), as it is clearly stated in the Qur'an and Hadith, as one of the things that must be preserved. This is after hifz al-din (preservation of religion), hifz al-nafs (preservation of the soul), hifz al-'aql (preservation of reason), hifz al-nasl (preservation of offspring), and hifz al-mal (preservation of property). This study also mentions one by one the concepts and forms of green economy implementation, which are related to hifz al-din, hifz al-nafs, hifz al-'aql, hifz al-nasl, hifz al-mal, and hifz al-bi'ah in detail, in accordance with studies in Islamic economics. Keyword: green economy, maqashid al-shariah, environment